Synergisticity of Family, School, and Community Education In Strengthening Religious Moderation - Daheri, Mirzon; Rohimin, Rohimin; Amin, Alfauzan; Iqbal, Moch; Warsah, Idi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThis research aims to analyze how the synergy between family, school, and community education can strengthen the understanding and practice of religious moderation and the supporting factors, forms, and effects of this synergy. The research was conducted at Sindang Jati, Rejang Lebong, Bengkulu using qualitative methods and a phenomenological approach. The data collection technique used snowball sampling for interviews, accompanied by observation and documentation. The data were analyzed with a phenomenological model through epoch and ideation. The research results show that close collaboration between education received in the family, at school, and in society can significantly improve understanding and practice of religious moderation. These findings confirm that the synergy between these three components provides a large positive impact, in line with the social theory proposed by Parson and Brofenbrenner. Factors such as shared goals, effective communication (associative interaction), parental involvement, school commitment, and community trust and roles are essential in strengthening this synergy. In line with Murphy's law, the synergy of the three educational centers minimizes opportunities for immoderate attitudes and actions to grow.AbstrakTujuan penelitian ini untuk menganalisis bagaimana sinergisitas antara pendidikan keluarga, sekolah, dan masyarakat dapat menguatkan pemahaman dan praktik moderasi beragama, faktor-faktor pendukung, bentuk dan pengaruh sinergisitas tersebut. Penelitian dilakukan di Sindang Jati, Rejang Lebong, Bengkulu dengan menggunakan metode kualitatif dan pendekatan fenomenologi. Teknik pengambilan data menggunakan snowball sampling untuk wawancara, disertai observasi dan dokumentasi. Data dianalisis dengan model fenomenologi melalui epoche dan ideation. Hasilnya menunjukkan sinergisitas antara pendidikan keluarga, sekolah, dan masyarakat dapat membantu meningkatkan pemahaman dan praktik moderasi beragama selaras dengan teori sosial Parson dan Brofenbrenner. Faktor-faktor seperti kesamaan tujuan, komunikasi yang efektif (interaksi asosiatif), keterlibatan orang tua, komitmen sekolah, dan kepercayaan serta peran masyarakat, merupakan hal yang penting dalam memperkuat sinergi ini. Selaras dengan hukum Murphy bahwa sinergisitas tiga pusat pendidikan meminimalisir peluang sikap dan tindakan yang tidak moderat untuk tumbuh. How to Cite: Daheri, M., Rohimin, Amin, A., Iqbal, M., Warsah, I. (2023). Synergisticity of Family, School, and Community Education In Strengthening Religious Moderation. TARBIYA: Journal of Education in Muslim Society, 10(1), 103-122. doi:10.15408/tjems.v10i1. 36028.